ANALYSIS OF ERRORS IN READING ARABIC TEXTS AMONG MALDIS STUDENTS: ANALISIS KESALAHAN DALAM MEMBACA TEKS BERBAHASA ARAB PADA MAHASANTRI MALDIS - Solehudin, Muhammad Oleh; Hadi, Abdul; Lathifah Fauzia, Eva (Jurnal Kata, 2025)
Difficulties in determining I’rab in modern Arabic texts are still frequently encountered in the learning process, particularly by MALDIS students. This is due to a lack of understanding in correctly applying the rules they have learned to the text. This study involved 30 students with the aim of analyzing the types of I’rab errors, identifying the most frequently misapplied rules, and determining the underlying causes. Additionally, this study implemented an instructional intervention to gradually reduce the error rate. The method used was qualitative descriptive with the listen-and-note technique. Pre-test results showed 368 errors (68.4%), primarily in the rules of idhafah, jar majrur, and fa’il. After the intervention, the number of errors in the post-test decreased to 170 (31.6%), indicating a significant improvement in the students’ proficiency. These findings underscore the importance of appropriate learning strategies in helping students understand I’rab. This study also contributes to the development of more effective and practical Arabic teaching methods. Further research is recommended to employ different methods and involve a broader sample of participants to ensure the results are more generalizable and applicable across various learning contexts.